Entrepreneurship education: an evaluation of the Young Enterprise Wales initiative - Paul Jones (Education + Training, 2013)
The purpose of this paper is to present an evaluation of the impact of the Young Enterprise Wales (YEW) programme on its participants. YEW represents the Wales region of the programme which is an annual competition to assist 15-19-year-old secondary school pupils acquire entrepreneurial skills through running a business.The paper utilises a semi-structured data collection method within which attitudes, impacts and perceptions of the YEW programme are assessed. In total, 44 participants in a YEW regional final were interviewed and a questionnaire completed. The results indicated a positive participant reaction to the YEW programme with an affirmative response to all questions regarding the impact and experience of the course. The post final results suggested that the programme has improved entrepreneurial competencies and the future potential for business start-up. The paper recognises that the research respondents were drawn from one region of the UK and were successful participants in the programme. Further evidence is required to assess the longitudinal impact upon future entrepreneurial behaviour on these individuals. The paper contributes to knowledge by adding to a limited literature examining the impact of entrepreneurship education within the 16-19 secondary school age sector. The essential elements of the YE experience are identified and proposed as a model for best practice for enterprise education at this age group. The paper contributes to knowledge by adding to a limited literature examining the impact of entrepreneurship education within the 16-19 secondary school age sector. The essential elements of the YE experience are identified and proposed as a model for best practice for enterprise education at this age group.